PENGEMBANGAN APLIKASI ZOTERO DALAM PENULISAN KARYA ILMIAH DI PERPUSTAKAAN UIN IMAM BONJOL PADANG - Jendri (Jurnal Al- Ma'arif : Ilmu Perpustakaan dan Informasi Islam, 2023)
This research is a development of the zotero application in writing scientific papers with the aim of providing information and facilitating writers in writing scientific papers such as theses, journals, dissertations and so on, so that the presence of the zotero application provides manifestation in writing. The method used in this research uses a qualitative approach and descriptive method. provide descriptions and present research data that has been analyzed. The technical data collection in this research is descriptive and then manages it with analytical techniques which will be formulated in the form of words not numbers. The results of this study indicate that Zotero is a reference manager that can be used free of charge which makes it easier for writers to manage sources in writing and referrals. Zotero application is obtained free of charge which has the ability to detect the content available on a web page, and store it via a computer as a library.